Interaction Between Cecal Metabolites and Liver Lipid Metabolism Pathways During Induced Molting in Laying Hens - Zhang, Jun; Geng, Xiaoqing; Zhang, Yihui; Zhao, Xinlong; Zhang, Pengwei; Sun, Guirong; Li, Wenting; Li, Donghua; Han, Ruili; Li, Guoxi; Tian, Yadong; Liu, Xiaojun; et al. (Frontiers in Physiology, 2022)
ABSTRACT Moult is a normal physiological phenomenon in poultry. Forced moult (FM) induced by feeding stop-feeding is the most widely used and economical technique. By forcing moult, the laying hens develop propranolol feathers and improve laying performance during the next laying cycle. However, the lack of energy supply has a huge impact on both the liver and intestines, and acts on the intestines and liver through the "gut-liver axis". More importantly, lipid metabolism in liver is closely related to reproductive performance of laying hens. Therefore, in this study, cecal metabolites and liver transcriptome data during forced molting of laying hens at the late stage of laying (stop feeding method) were analyzed together to reveal the regulatory mechanism of "intestinal-liver axis" affecting the reproductive performance of laying hens from the perspective of lipid metabolism. Transcriptome analysis revealed that 4796 genes were obtained, among which 2784 genes had significant differences (P<0.05). 49 genes were associated with lipid metabolism, and 5 core genes (AGPAT2, SGPL1, SPTLC1, PISD and CYP51A1) were identified by WGCNA. A total of 96 differential metabolites were obtained by correlating them with metabolome data. FM affects laying performance by regulating genes related to lipid metabolism, which in turn regulates cholesterol and steroid metabolism. This experiment not only enriched the theoretical basis of forced moulting, but also provided theoretical basis for the treatment of human fatty liver and the study of "enteric-liver axis".